Cell and Molecular Biology: How the Role of Technology in Medical Laboratories - Nurjannah Achmad (Institute of Computer Science (IOCS), 2022)
Medical laboratories have a strategic position because they support several important roles, especially in terms of examination services in the fields of Hematology, Clinical Chemistry, Clinical Microbiology, Clinical Parasitology, Clinical Immunology or other fields related to individual health interests, especially to support efforts to diagnose disease, cure disease and health restoration. This research was conducted by conducting a search on several relevant literature studies with the focus of research focused on the role of technology in medical laboratories, with the results of the study explaining that the information system contained in a medical laboratory certainly involves several important elements in it such as, patients, laboratory staff. , and a medical laboratory technologist. Providing detailed information is one of the efforts that must be made for the satisfaction of patients in accessing various information related to the history or clinical symptoms that they are suffering from. In addition, medical laboratory information systems are needed to improve the performance of employees and health organizations with the aim of increasing work productivity, adding new computerized integrated services to make it easier for users to collect, process and present data in as much detail as possible, easy to understand and timely. The medical laboratory as a medical support service unit is expected to be able to provide accurate and accurate information about the laboratory aspects of specimens/samples whose tests are carried out in the laboratory by a Medical Laboratory Technologist (ATLM).